IMPLEMENTASI SENSOR ULTRASONIK PADA TEMPAT SAMPAH PINTAR BERBASIS IOT - Verryando, Krissantus Andrie; Iskandar, Riyadi J.; Arthadi Putra, Alfred Yulius (INTEKSIS, 2024)
The increasing problem of waste management has become a global issue that requires innovative solutions. The main cause of this issue is the awareness of each person. In today's digital era, smartphones are a top priority in doing activities because efficiency becomes a convenience as any example is within reach. The ease of getting information becomes a reference in making decisions. The rise of technology that is increasingly sophisticated in the last decade has made everything around us also touch technology according to the needs of its users. In this regard, this research aims to design and implement a smart trash can connected through the Internet of Things (IoT) using ultrasonic sensors. The system is designed to automatically open and close the trash can, detect the presence of users who will throw away the trash, detect the level of trash can contents, send data to the Telegram application, and provide notification of almost full trash can notifications to users in real- time or manually by interacting through a chatbot on the Telegram application according to the data sent by the ultrasonic sensor. This research uses hardware and software design approaches and quantitative methods. Arduino Uno R3 is used as a microcontroller that works as an electronic circuit capable of processing data and changing it as a reaction to open and close the trash can automatically. The ultrasonic sensor is used to detect the user and measure the level of the bin contents, and the electronic components connected through the IoT network send the data to the Telegram application. A web-based application and a mobile application were developed for the bin monitoring system that is useful for monitoring the status of the bin and providing notifications to users. The results showed that the system was successful in detecting the content level of the bin with a high degree of accuracy. The use of IoT technology enables efficient monitoring and better decision- making in waste management. In addition, the use of these smart bins can help reduce user manual labor and optimize garbage collection in the neighborhood. Keywords - Internet of Things (IoT), Smart Trash Can, Monitoring System, Ultrasonic Sensor, Telegram